ASSESSMENT OF FEET AND RISK CLASSIFICATION FOR DIABETIC FOOT: NURSING CONTRIBUTIONS - Eduardo Godoi Audi; Ricardo Castanho Moreira; Ana Cândida Martins Grossi Moreira; Eliana de Fátima Catussi Pinheiro; Maria de Fátima Mantovani; Arlinda Gonçalves de Araújo (Universidade Federal do Paraná, 2011)
The objective was to study the degree of risk for diabetic foot among diabetics on the HIPERDIA system. An epidemiological-descriptive quantitative approach was chosen, with data obtained by field research between January and April 2010. Fifty people diagnosed with diabetes were selected for the study, all resident in the area attended by the Basic Health Unit of the study. The majority of participants were women, between the ages of 50 and 69, who had suffered from diabetes for between 5 and 9 years. The degree of risk 0 included the largest number of people, with 56%, although there were others who already had ulcers and lower member amputations, these people being classified as risk 3. The risk stratification permits the prioritization of groups of people in order to better allocate the necessary health care resources.